Instrumen E-Test Sebagai Inovasi Penilaian Berbasis Website - Kamila, Saifiyatil; prihatiningtyas, suci (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
The use of information and communication technology in the field of education has changed the paper-based manual assessment system into an online assessment using a website. Paper-based assessment is considered less effective because it takes a lot of money, time, place and personnel in its implementation and there are still acts of student cheating in carrying out the exam. Therefore, it is necessary to make a breakthrough in the assessment that utilizes the website. The method used in designing this web-based exam system is the waterfall method. The E-Test instrument as a website-based assessment innovation is expected to be one of the breakthroughs in administering the Exam that is able to reduce operational costs, time, and reduce fraudulent actions.